Kajian Optimasi Kapasitas Danau Tempe untuk Mengurangi Banjir di Kabupaten Sidrap, Kabupaten Soppeng, dan Kabupaten Wajo - Provinsi Sulawesi Selatan - Agustin Purwanti; Roni Farfian; Chairunnisa; Rifaldi Aji Sarifudin; Aditya Wisnu M.P (Fakultas Teknik - Universitas Jenderal Achmad Yani, 2022)
Tempe Lake is a floodplain lake in South Sulawesi Province. The capacity of Tempe Lake is affected by the inflow into the lake. The high intensity of rain causes the lake water to overflow and flood the area around the lake. To reduce the flood inundation, an optimization study was carried out on the capacity of Tempe Lake. Optimization is carried out by adjusting the optimal height of the gate opening on the Tempe Moveable Weir using a hydrological model. The curve number (CN) of rivers flowing into the lake is used, which is a function of 2 land cover scenarios, namely the existing condition and the RTRW plan for South Sulawesi Province. Based on hydrological modeling, it was found that the inflow of Tempe Lake (Q25) for the existing condition scenario was 11,825.83 m3/s, and for the RTRW plan of South Sulawesi Province, scenario was 11,606.62 m3/s. The 2D hydrodynamic modeling simulates various heights of gate openings on the Tempe Moveable Weir with respect to the flood inundation area. The optimal capacity of Tempe Lake to reduce flooding is achieved by maintaining the water level at +7.53 m above sea level with a gate opening height of 4 m.